2022
DOI: 10.1145/3490494
|View full text |Cite
|
Sign up to set email alerts
|

The Making of Meaning through Dyadic Haptic Affective Touch

Abstract: Despite the importance of touch in human–human relations, research in affective tactile practices is in its infancy, lacking in-depth understanding needed to inform the design of remote digital touch communication. This article reports two qualitative studies that explore tactile affective communication in specific social contexts, and the bi-directional creation, sending and interpretation of digital touch messages using a purpose-built research tool, the Tactile Emoticon. The system comprises a pair of remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…In agreement with our first hypothesis, the geographically separated romantic couples that participated in this study reported a significant increase of overall social connectedness levels after using the haptic bracelets in daily life for a period of 2 weeks. This result is also in line with similar findings from studies that were performed for a briefer period and in restricted (laboratory) conditions (Visser et al, 2011;Park et al, 2013;van Erp and Toet, 2015;Price et al, 2022).…”
Section: Social Connectednesssupporting
confidence: 90%
See 3 more Smart Citations
“…In agreement with our first hypothesis, the geographically separated romantic couples that participated in this study reported a significant increase of overall social connectedness levels after using the haptic bracelets in daily life for a period of 2 weeks. This result is also in line with similar findings from studies that were performed for a briefer period and in restricted (laboratory) conditions (Visser et al, 2011;Park et al, 2013;van Erp and Toet, 2015;Price et al, 2022).…”
Section: Social Connectednesssupporting
confidence: 90%
“…As such, KE and SU may not be affected by MST technology when implemented in an isolated fashion, and perhaps a more multimodal approach of testing this kind of technology (e.g., combined with mediated audio/visual cues) may influence these dimensions of social connectedness. Work by Price et al ( 2022 ) underscores this notion and illustrates how multimodal haptic signals (e.g., temperature) could also play a role here. Still, the thinking of the other subtheme from the TA illustrates how, even with a low-bandwidth signal, and lack of other (haptic) modalities, participants ascribed specific meaning to receiving a haptic signal through the bracelets and had specific intentions when sending signals.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Handshake: A Gripping History by Al-Shamahi (2021), and Out of Touch, by Druin (2022). Touch has been shown to be an effective means of influencing people's attitudes and creating bonds with people and places (Price et al, 2022): themes explored by Golmohammadi, Samuelsson, and Cohrt in their contributions. Interpersonal touch has been shown to improve information flow and to result in a more favourable evaluation of communication partners and to increase compliance (Field, 2003).…”
mentioning
confidence: 99%